The role of fiscal and monetary policy in Nigeria's industrialisation 1956-1966 - Awosika, K. A.; University of Oxford ([S.l.] : University of Oxford, 1973)
Chapter 1-4 of this thesis discusses the factors for influencing the adoption of industrialization as a means of promoting economic growth, the objectives of the industrialization policy and the financial methods by which it has been pursued. Chapter 5-8 is devoted to monetary policy.
Includes bibliographical references
ahz 18/03/2019
Loans
Keywords: Monetary policy; Industrialization; Nigeria